2003
DOI: 10.1007/s00384-002-0472-x
|View full text |Cite
|
Sign up to set email alerts
|

Prospective study of artificial anal sphincter and dynamic graciloplasty for severe anal incontinence

Abstract: Background and aims:Dynamic graciloplasty and artificial anal sphincter are two options for refractory incontinence, the efficacy of which was compared in a prospective study. Patients and methods: Between November 1966 and June 1998, 16 patients were operated on (artificial anal sphincter 8, dynamic graciloplasty 8). Four consecutive operations with each technique were performed by two colorectal surgeons (one initiated the study with the neosphincter and the other with dynamic graciloplasty). Two independent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2005
2005
2017
2017

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(16 citation statements)
references
References 18 publications
0
16
0
Order By: Relevance
“…Though the ABS was found to be more effective in improving continence scores. 41 However, larger long-term studies are needed.…”
Section: Discussionmentioning
confidence: 99%
“…Though the ABS was found to be more effective in improving continence scores. 41 However, larger long-term studies are needed.…”
Section: Discussionmentioning
confidence: 99%
“…34 A small single-center prospective study comparing the artificial bowel sphincter to graciloplasty for fecal incontinence slightly favored the artificial bowel sphincter, but complications were common in both groups. 35…”
Section: Management Of Rectal Injuriesmentioning
confidence: 99%
“…46 A prospective controlled study comparing dynamic graciloplasty with artificial anal sphincter in 16 patients 8 in each group showed that both of the two procedures had a high incidence of technical failures and complication requiring re-operation. 47 Chapman et al 48 reported a systematic review article of this procedure, where they searched articles published until November 1999, and found 40 articles met the inclusion criteria. Mortality rates were around 2% for both graciloplasty and colostomy.…”
Section: Surgical Treatmentmentioning
confidence: 99%